La valeur de la connaissance des émotions - De Vlieger, Bertille (Labyrinth, 2019)
The Value of the Emotional Knowledge Emotional knowledge is a form of self-knowledge which holds great interest for ordinary individuals. It is not obtained by any obligation but rather because we think it is crucial to obtain (Cassam 2017). In this article it is a matter of demonstrating that emotional knowledge holds an instrumental and a prudential value. By arguing that it can allow a control over our emotions, I shall maintain that emotional knowledge affects individual marginalization or acceptance in society. In addition, this type of knowledge is revealing of our personality by allowing us to identify our affective identities. Finally, I shall defend the idea that emotional knowledge contributes to the conduct of a good life. As such, my hypothesis could be viewed as incompatible with widespread ideas (Montaigne 2019), according to which the knowledge of our own emotions can trigger negative emotional states, e.g. mental rumination, anxiety, that do not contribute to our well-being.